Computational intelligence and intelligent systems. 9th International Symposium, ISICA 2017, Guangzhou, China, November 18-19, 2017, revised selected papers /: 9th International Symposium, ISICA 2017, Guangzhou, China, November 18-19, 2017, revised selected papers. Part I : (2018) - Unknown
No abstract available